The Effect of Carbon Emission Disclosure and Environmental Information Disclosure on Company Value With Commissioner Size as Moderation - Fiona Wiryawan (PT. Publikasiku Academic Solution, 2023)
This research aims to determine the effect of disclosure of carbon emissions and environmental information on firm value with board size as a moderating variable. Disclosure of carbon emissions is a form of corporate transparency to shareholders in the context of overcoming global warming and climate change. This is also believed to increase the value of the company in the long term. The population used in this study are non-financial companies at LQ 45 which are listed on the Indonesia Stock Exchange in the period August 2022 to January 2023. This research method is quantitative using purposive sampling. Based on analysis data, the disclosure of carbon emissions and the disclosure of environmental information have significant positive results on the value of the company. On the other hand, the size of the board of commissioners is still unable to moderate the disclosure of carbon emissuons and disclosure of environmental information on the value of the company.